2019
DOI: 10.1002/cam4.2012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of breast cancer risk factors among molecular subtypes: A case‐only study

Abstract: Epidemiological studies have a clear definition of the risk factors for breast cancer. However, it is unknown whether the distribution of these factors differs among breast cancer subtypes. We conducted a hospital‐based case‐only study consisting of 8067 breast cancer patients basing on the Tianjin Cohort of Breast Cancer Cases. Major breast cancer subtypes including luminal A, luminal B, human epidermal growth factor receptor 2 (HER2)‐enriched and basal‐like were defined by estrogen receptor, progesterone rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 39 publications
7
37
0
1
Order By: Relevance
“…Previous studies among Chinese women have examined the associations between menopausal status and various combinations of molecular markers of breast cancer. A recent study consisting of 8067 Chinese women focused on the same molecular subtypes of breast cancer with us and demonstrated that postmenopausal women tended to have HER2‐overexpressing and triple‐negative subtypes . Also consistent with our study, another study on Northeast Chinese women found that postmenopausal status decreased the odds of luminal A and luminal B subtypes compared to controls .…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies among Chinese women have examined the associations between menopausal status and various combinations of molecular markers of breast cancer. A recent study consisting of 8067 Chinese women focused on the same molecular subtypes of breast cancer with us and demonstrated that postmenopausal women tended to have HER2‐overexpressing and triple‐negative subtypes . Also consistent with our study, another study on Northeast Chinese women found that postmenopausal status decreased the odds of luminal A and luminal B subtypes compared to controls .…”
Section: Discussionsupporting
confidence: 90%
“…The higher prevalence of the Her2 subtype in our cohort, the South Korean and the TCGA Asian cohorts is consistent with immunohistochemistry-based epidemiological studies among Asians and Asian Americans 46 49 . It is becoming increasingly apparent that the lifestyle and genetic risk factors may have overlapping but sometimes distinct effects in different subtypes of breast cancer.…”
Section: Discussionsupporting
confidence: 90%
“…The results showed that age (OR =1.05, 95% CIs: 1.03 to 1.08) was an independent predictor. Many previous studies have shown that family history is strongly associated with breast cancer [22][23][24], even in multivariate regression, family history (OR =7.13, 95% CIs: 0.62 to 82.03) with P=0.1125, the number of first-degree relatives with history of breast cancer was an independent predictor and was forced to be incorporated into the logistic regression analysis. The formula of Linear Predictor = -4.78455 +0.04167*Age +1.96384*(family history=1).…”
Section: Clinical Predicted Nomogrammentioning
confidence: 99%